Prevalence of non-infectious masses on intracardiac devices as incidental finding during transoesophageal echocardiography. (3rd October 2022) - Kuecken, T; Jasaityte, R J; Haase-Fielitz, A H F; Butter, C B
Abstract: Background: Incidentally detected masses on the leads of cardiac implantable electronic devices (CIED) present a clinical dilemma and often raise the question whether they should be treated as a device infection. Indeed, they are considered as one of the major Duke criteria for the diagnosis of infectious device endocarditis. However, rather often incidental lead masses are detected in a routine transesophageal echocardiography (TOE) in patients without any signs of infection. Data on the prevalence of such findings are scarce and outdated. Purpose: In this study, we aimed to determine the current prevalence and predisposing clinical factors of incidental non-infectious lead masses. Methods: In this retrospective single center study, we analyzed all TOE examinations performed between 2020 and 2021 for the indications other than suspected infectious endocarditis. Patients with nonsuspicious leads and the ones with incidental non-infectious lead masses were compared with regard to clinical characteristics, presence of anticoagulation and indication for TOE. Results: In total, 1361 TOE examinations were performed within the study period. From those 141 patients with CIED were selected. Thirty-nine patients (27.6%) presented with non-infectious CIED masses. The clinical characteristics of study patients and the TOE indications are listed in Table 1. Patients with incidental CIED mass showed a higher prevalence of dilated cardiomyopathy (38.5%) compared to patients with no CIED mass (16.7%), p=0.004 Table 1. The presence of laboratory sings of infection and cardiovascular risk factors, such as arterial hypertension, diabetes mellitus or chronic kidney disease did not differ significantly between both groups (Table 1). Also, incidental lead masses were less prevalent in patients with oral anticoagulation (Odds ratio 0.33, 95% CI: 0.11–1.00; p=0.048; Figure 1), whereas the distribution of CHA2DS2-VASc Scores did not show any differences. Conclusion: The prevalence of incidental non-infectious CIED lead masses in TOE in our study was 27, 6%, which is higher, than previously reported 5–10%. We did not observe any association between the incidental CIED lead masses and cardiovascular comorbidities. The absence of the oral anticoagulation seems to be the only clinical risk factor for such findings in our study, suggesting possible thrombogenic genesis. The high prevalence of incidental non-infectious lead masses should be kept in mind in order to avoid the overdiagnosis of CIED infection and unnecessary lead extraction. Funding Acknowledgement: Type of funding sources: Public hospital(s).